MATHEMATICS-BASED TEACHING MODEL AND INSTRUCTORS’ FINANCIAL ACCOUNTING PERFORMANCE: AN EXPERIMENTAL STUDY - Warsono, Sony; Rohma, Frida Fanani; Pranesti, Arin; Rumiyati, Rumiyati (UI Scholars Hub, 2023)
Double entry bookkeeping (DEB) and the rules of debit and credit (RDC) are first contained in a mathematical book. Using this basic premise, this study develops a mathematics-based teaching model (MBTM) and examines its impact on instructors’ financial accounting performance. This study employed a quasi-experimental method with 43 accounting instructors as participants. The findings indicate that the implementation of the MBTM resulted in a significant improvement in instructors' performance. Furthermore, the teaching experience had a positive effect on instructor performance, particularly when combined with the MBTM approach. Previous empirical research has aimed to compare traditional (preparer) and innovative (user) teaching approaches for the introductory accounting course. In line with this objective, the present empirical study introduces the MBTM as an innovative teaching model and assesses its effectiveness. This study is the first of its kind to implement the innovative mathematics-based teaching model (MBTM) specifically designed based on the history of accounting. It is worth noting that the study also utilized accounting instructors as research subjects, a less commonly employed approach in previous research endeavors.